Shell Company - Al-Saffar, Zeina Ghanem (Journal of Legal and Political Studies, 2015)
mock is a company established by the person or entity to create following legal action by the legislator in the commercial companies law registration and publicity in the form of a partnership or limited partnership or limited liability company, this is what appears to others, but the reality was quite different from the apparent situation, because this company has is just one person and there are in fact partners. The owner to have the legal framework and it (the company) to take advantage of corner polygamy for partners and required by federal law, the plurality of my photos or a placebo is not a real company, and the company's share capital is owned by only one person is the owner of the project. and take the path to the establishment of the company is part owner of the business does not have a kiss only or for certain banking facilities, or that national law prevents foreign owned businesses alone. and this raises several problems, most notably the extent of the responsibility of members of the company's debt paper, and what impact the company's actions in the face of others goodwill that is not aware of the fact the company which violates the trade credit component of the business life.
Keywords: commercial companies law; business; legal framework; credit